The Effect of Project-Based Learning Model and Learning Motivation on Writing Anecdotal Text Skills of Grade X Students - Ega Septiviana; Abdurrahman (Indonesia Approach Education, 2024)
There are still problems in writing anecdote text because it requires a critical thought process. Based on the problem, this study aims to determine the effect of the Project-Based Learning model on the ability to write anecdotal text, then see the effect of student motivation, and finally see the form of interaction of the two independent variables on the dependent variable. The type of research used is quantitative with a pseudo-experimental method. The population of this study were grade X students of UNP Laboratory Development High School who were enrolled in the 2022/2023 academic year. The sample of this study were students of class X.B as an experimental class and X.A as a control class. The results showed that 1) the Project-Based Learning model influenced students' ability to write anecdotal text, 2) motivation does not affect students' ability to write anecdotal text, and 3) there is no interaction between the Project-Based Learning model and students' learning motivation.